Exploring global perspectives on income inequality research - Nur Aliyah Jazuli; Assis Kamu; Diana Hassan; Ho Chong Mun (Karya Ilham Publishing, 2025)
Income inequality remains a pressing global issue, particularly in developing nations, emerging economies, and even advanced countries where wage gaps, wealth concentration, and social context challenges develops. Consequently, this paper conducts a bibliometric analysis of income inequality research to identify the key trends, influential authors, productive countries, and significant publications. Using data from Scopus and tools like Hazing Publish or Perish, VOS viewer and Bibliophagy, we examined 456 publications from 1982 to 2025 through performance analysis and science mapping. Findings reveal a significant rise in re-search output after year 2015, with strong relationships between income inequality with pub-lic policy, health, and sustainability.